Sri Lankan Tamil Refugees in India: Conceptual Framework of Repatriation Success - George, Miriam; Vaillancourt, Anita; Rajan, S. Irudaya (Refuge: Canada's Journal on Refugees, 2016)
Repatriation to Sri Lanka has become a primary challenge to Sri Lankan Tamil refugees in Indian refugee camps, and a matter of significant public discussion in India and Sri Lanka. Anxiety about repatriation among Sri Lankan Tamil refugees and lack of initiation from the Sri Lankan government threatens the development of a coherent repatriation strategy. This article proposes a conceptual framework of repatriation success for Sri Lankan Tamil refugees, which the Sri Lankan government, non-governmental agencies, and Sri Lankan Tamil refugees may use to develop a concrete strategy for repatriation. Based upon the study results of two of the authors’ repatriation studies, this article identifies and describes the four key concepts of the repatriation framework: livelihood development, language and culture awareness, social relationships, and equal citizenship within a nation.